Peranan Media Pembelajaran Berbasis Video Animasi pada Materi Sistem Pencernaan Manusia di SMP: Pemahaman Dampak dan Gangguan Sistem Pencernaan - Gulo, Joycellin Gabriela; Zebua , Della Krisno; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to determine the role of animated video-based learning media on human digestive system materials (understanding the impact and disorders of the digestive system) in junior high schools. The research method used is the Systematic Literature Review (SLR) method. In this study, the Systematic Literature Review (SLR) method was used, data collection in this study, using literature studies published in national journal articles that have been registered in electronic databases and indexed on google scholar. The data analysis process is carried out qualitatively consisting of data reduction, data presentation, and drawing conclusions. The results of the study are that through the media of animated videos, students can observe audio-visually the process of the human digestive system in the body more clearly and really. Animated videos have the advantage of attracting attention, providing aesthetic pleasure, supporting systematic learning, making it easier for students to understand, and can explain content that is difficult for students to understand. In this animated video, students can visually see how the shape of the organs in the body that play a role in the digestive process, from converting food into a source of energy to becoming feces that are ready to be excreted